Macroeconomic Factors and SENSEX Performance in India : Unveiling the Post-Liberalization Era (1980 – 2020) - Bonelli, Marco I. (Indian Journal of Research in Capital Markets, 2023)
Background : One of the world’s largest developing nations, India, has seen tremendous economic progress since the Liberalization Reforms in 1991, but rather than functioning independently, the market was impacted by several macroeconomic factors that were active simultaneously. Purpose : The study examined how various macroeconomic factors have affected the SENSEXâ€™s performance in India between 1980 and 2020. Methodology : Secondary data regarding the stock market and the Reserve Bank and World Bank reports have been considered. Findings : The Indian stock market and inflation were inversely correlated, while GDP growth and inflation were directly correlated. The foreign currency rate varies with respect to US dollars. Practical Implications : This research filled in important gaps in the literature regarding the relationship between the stock market, macroeconomic factors, and economic development. It also offered suggestions for investors and organizations on how to analyze and forecast the movement of Indian stock markets, as well as theoretical insights for future forecasts. Research Originality : While the previous research has addressed the singular impact of variables or included the pre-liberalization period, this study has provided an analysis of stock market data using multiple macroeconomic factors during the post-liberalization period.